Evaluation of four sorghum hybrids through the development of sorghum flour tortillas - Fernholz, Mary C. (Kansas State University, 2008)
With an increasing number of people with celiac disease, the need for gluten-free products is inevitable. Sorghum is a grain safe for celiac patients. Therefore, the purpose of this work was to characterize four sorghum hybrids in terms of their grain and flour; then utilize the hybrids in a wheat-free product and test for physical, chemical, textural, and sensory differences. Flour tortillas were chosen for their current popularity and the lack of research and availability for gluten-free flour tortillas. Grain characterization included diameter, weight, and hardness as measured by the Single Kernel Characterization System and Tangential Abrasive Dehulling Device. Flour characterization included flour and starch particle size distributions, total starch, amylose content, starch pasting properties, moisture, crude protein, and ash content. Significant differences were found (p<0.05) among hybrids for each test except total starch. Gluten-free flour tortillas were made from the four sorghum hybrids in addition to a commercial sorghum flour. Tortilla weight, diameter, thickness, color, pH, Aw, and moisture content were measured along with extensibility and stretchability. A descriptive panel was trained and used to analyze the five samples. Significant differences were found (p<0.05) among samples for color, pH, Aw, and moisture content. Significant differences were also found (p<0.05) among samples for extensibility and stretchability. Extensibility was a more effective test in studying quality. The sensory panel found significant differences (p<0.05) for grain specks, angle of bend, rancidity, sweetness, springiness, hardness, and grittiness. The commercial flour had the highest score for angle bend and springiness and was, therefore, utilized in a consumer study. When compared to a gluten-free wrap already in the market, the sorghum flour tortilla made from this study scored significantly higher in all attributes, including overall acceptability. The commercial flour is thought to have preformed better than the other four samples due to its smaller particle size and greater starch damage allowing an increase in water absorption.
Keywords: sorghum; gluten free; tortillas; sorghum tortillas; Agriculture, Food Science and Technology (0359)